Variability in Prebiotic Carbohydrates in Different Market Classes of Chickpea, Common Bean, and Lentil Collected From the American Local Market - Siva, Niroshan; Thavarajah, Pushparajah; Kumar, Shiv; Thavarajah, Dil (Frontiers in Nutrition, 2019)
Pulse crops such as lentil, dry bean, and chickpea are rich in protein, low digestible carbohydrates, and range of micronutrients. The detailed information of low digestible carbohydrates also known as ‘prebiotic carbohydrate” profiles of commonly consumed pulse market classes and their impact on human health are yet to be studied. The objective of this study was to determine the profiles of prebiotic carbohydrates [simple sugars, sugar alcohol (SA), raffinose family oligosaccharides (RFO), fructooligosaccharides (FOS), hemicellulose, cellulose, resistant starch (RS), and amylose] in two commonly consumed lentil market classes, seven dry bean market classes, and two chickpea market classes. After removing fat and protein, total carbohydrates averaged 54 g/100 g for lentil, 60 g/100g for dry bean, and 58 g/100g for chickpea. Among the portion of total carbohydrates, lentil showed 12-15 g/100g of prebiotic carbohydrates (sum of all prebiotic carbohydrates mentioned above), 18-21 g/100 g in dry bean, and 15-17 g/100 g in chickpea. Prebiotic carbohydrate concentrations within the market classes for each crop were significantly different (P < 0.05). Further, these pulses (lentil, dry bean, and chickpea) provide approximately 69 to 95% of the daily requirement of prebiotic carbohydrates (20 g/day) in a single serving. In conclusion, these three pulses are rich in prebiotic carbohydrates, however further increase of these healthy carbohydrates is possible by selecting diverse genetic mapping populations towards nutritional biofortification, and location sourcing towards increased prebiotic carbohydrate quality for human health.